Jejunal Perforation: A Rare Presentation of Burkitt’s Lymphoma—Successful Management - Samir Ranjan Nayak; Ganni Bhaskara Rao; Subramanya Sarma Yerraguntla; Sisir Bodepudi (Case Reports in Oncological Medicine)
Malignant tumors of the small bowel presenting as acute abdomen are a rare occurrence. Burkitt’s lymphoma presenting as a surgical emergency needing emergency laparotomy is an uncommon presentation of this tumor. We present an interesting case of jejunal perforation as a first manifestation of Burkitt’s lymphoma which was successfully managed with surgical resection, high dose chemotherapy, and good supportive care.